Pengaruh Digital Marketing dan Pelayanan terhadap Kepuasan Konsumen Jasa Travel Umrah - Syifa Fitriyatul Aini; Boyke Nugrahanto (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of digital marketing and service quality on consumer satisfaction in Umrah travel services at PT Hikayatuna Berkah Selalu, Bandung Regency. The increasing competition in the Umrah travel industry requires companies to optimize digital marketing strategies and improve service quality to maintain customer trust and satisfaction. This research applies a quantitative method with descriptive and verificative approaches. The population consists of all Umrah pilgrims in 2025, with a sample of 50 respondents selected using Slovin’s formula. Data were collected through questionnaires and analyzed using multiple linear regression, correlation analysis, coefficient of determination, and hypothesis testing (t-test and F-test). The results indicate that digital marketing has a positive and significant effect on consumer satisfaction (t = 3.643; sig = 0.001). Service quality also has a positive and significant effect (t = 3.495; sig = 0.001). Simultaneously, digital marketing and service quality significantly influence consumer satisfaction (F = 232.535; sig = 0.000) with an R² value of 0.807, meaning 80.7% of consumer satisfaction is explained by both variables. These findings imply that the integration of effective digital marketing strategies and high-quality service is essential to enhance customer satisfaction in Umrah travel services.